STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN BERBAHASA ANAK USIA DINI DI TK IT INSAN ROBBANI SIBUHAN: TEACHER'S STRATEGY TO IMPROVING EARLY CHILDHOOD LANGUAGE SKILLS IN IT INSAN ROBBANI SIBUHAN KINDERGARTEN - KHAIRU NISA YULIANTI; NUR AZIZAH LUBIS; JASMANI; DELFI ELIZA (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
The problem behind this research is improving teachers' learning strategies to enhance children's language proficiency. This study aimed to examine how teachers' techniques are used in the language development of TK IT Insan Robbani children. This study uses a descriptive, qualitative method. The data collection methods in this study are observational use and interviews. Data analysis techniques in this study are data reduction, data presentation, validation, and inference. The results of this study, which was found to be about teachers' strategies for developing children's language skills, explored teachers' direct communication methods, storytelling methods, visual media use, and checklist and anecdotal assessment of language development by providing.